Family Attachment and the Decision to Move by Race - Spilimbergo, Antonio; Ubeda, Luis. (Washington, D.C. : International Monetary Fund, 2002)
Blacks in the United States have a lower geographic mobility rates than whites even though they have several characteristics that are usually associated with high rates of mobility: high unemployment, low rate of home ownership, low marriage rate and settlement in areas where unemployment is high. This paper tests the relevance of family ties in explaining mobility by using proxies that are constructed using data from the University of Michigan's Panel Study of Income Dynamics, covering the period 1977-88. The results are robust to different specifications and estimation techniques, and explain the puzzle of the role played by the nuclear and the extended family in the decision to move.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet